The Effects of Perceived Islamophobia on Group Identification and Acculturation Attitudes. (7th May 2019) - Bastug, Mehmet F.; Akca, Davut
Abstract: This study examines the effects of perceived Islamophobia on group identification and acculturation attitudes in a sample of Turkish Canadians. We tested the rejection‐identification model (RIM) and the rejection‐disidentification model (RDIM) to examine how perceived Islamophobia affects religious and national identification. The study also explores whether perceived Islamophobia, national identification, and religious identification have any impact on the acculturation attitudes of Turkish immigrants. All relationships were investigated using path analysis. The results suggest that perceived Islamophobia does not affect religious or national identification. Results also show that perceived Islamophobia positively predicts endorsement of marginalization as an acculturation strategy. National identification predicts higher levels of integration and assimilation and lower levels of separation. Those who report higher religious identification are more inclined to prefer separation.